Inovasi Digitalisasi Pembiayaan Syariah: Solusi Akses Sertifikasi Halal UMKM - Ifa, Khoirum Rodhiatul; Anwar, Khairul (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
The purpose of this study is to examine and analyze the role and implementation of sharia financing digitization as a solution to improve access to halal certification for MSME business actors. This study uses a qualitative approach with a library research method. Data collection techniques were collected through systematic searches of journal repositories such as Google Scholar, official websites of institutions such as the OJK and Islamic Banks, as well as financial reports and policies from Islamic banking institutions. The data was analyzed using thematic content analysis, which involves identifying patterns, main ideas, and relationships between variables in the reviewed literature. The analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results indicate that digitalization innovations in Islamic financing for halal certification emerge as a solution that combines Islamic financial technology (fintech) with halal certification requirements. The implementation of Halal Go Digital not only provides direct benefits to SMEs but also has significant systemic impacts on the development of the national halal industry ecosystem. This research is expected to lead to the creation of more affordable and efficient access to halal certification for SMEs business actors.